Bidirectional multiwavelength Brillouin fiber laser generation in a ring cavity - Shirazi, Mohammadreza Rezazadeh; Biglary, Mozhgun; Harun, Sulaiman Wadi; Thambiratnam, K.; Ahmad, Harith (Institute of Physics, 2008)
Bidirectional multiwavelength Brillouin fiber laser (BFL) generation is demonstrated using a 25 km long single-mode fiber as a Brillouin gain medium in a ring cavity. Odd-order Brillouin Stokes waves appear in the backward direction whereas Brillouin pump and the even Stokes orders are in the forward direction with the line spacing 0.16 nm (∼20 GHz) between each two consecutive waves in forward and backward directions. In addition, by a combination of the backward and forward outputs, we have a higher number comb generation of a multiwavelength BFL with the line spacing 0.08 nm (∼10 GHz). The proposed configuration can work at any wavelength which is a benefit to the others.